MANAJEMEN RISIKO PROYEK BERDASARKAN PANDUAN BODY OF KNOWLEDGE MANAJEMEN PROYEK 2017 - Hifthario Syahputra; Willy Abdillah; Slamet Widodo; Syaiful Anwar (Jurnal Manajemen dan Bisnis, 2022)
This research aimed to describe and examine the project risk management in Wijaya Karya, Inc (WIKA) based on the provisions in Project Management Body of Knowledge (PMBOK) Guide 2017. Specifically, it describes and examines seven processes are plan risk management, identify risks, qualitative risk analysis, quantitative risk analysis, plan risk responses, implement risk responses and monitor risks in that construction company. This research is descriptive with qualitative approach. Methods of collecting data use observation, especially the direct observation (participant observation), in depth interview, especially the structured interview and documentation. The result of this paper showed that the description of the project risk management of the consruction company in Indonesia generally by applying a measurable risk threshold that provides an overview of WIKA’s risk appetite and project stakeholders. For risk appetite, the project team is guided by the provisions contained in the International Standards Organization (ISO) 31000 in 2009 and 2018 for risk appetite (as novelty). The description of the project risk management of the consruction company in Indonesia specifically has seven integrated processes. Those are project risk management, planning risk management, identify risks, qualitative risk analysis, quantitative risk analysis planning risk responses, implementation risk responses and monitoring risks. All processes have complied with the provisions in the 2017 PMBOK Guide.